Regional anesthesia and analgesia after surgery in ICU. Issue 5 (October 2017) - Capdevila, Mathieu; Ramin, Séverin; Capdevila, Xavier
Abstract : Purpose of review: The aim is to demonstrate that ICU physicians should play a pivotal role in developing regional anesthesia techniques that are underused in critically ill patients despite the proven facts in perioperative and long-term pain, organ dysfunction, and postsurgery patient health-related quality of life improvement. Recent findings: Regional anesthesia and/or analgesia strategies in ICU reduce the surgical and trauma–stress response in surgical patients as well as complications incidence. Recent studies suggested that surgical/trauma ICU patients receive opioid–hypnotics continuous infusions to prevent pain and agitation that could increase the risk of posttraumatic stress disorder and chronic neuropathic pain symptoms, and chronic opioid use. Regional anesthesia use decrease the use of intravenous opioids and the ectopic activity of injured small fibers limiting those phenomena. In Cochrane reviews and prospective randomized trials in major surgery patients, regional anesthesia accelerates the return of the gastrointestinal transit and rehabilitation, decreases postoperative pain and opioids use, reduces ICU/hospital stay, improves pulmonary outcomes, including long period of mechanical ventilation and early extubation, reduces overall adverse cardiac events, and reduces ICU admissions when compared with general anesthesia and intravenous opiates alone. The reduction of long-term mortality has been reported in major vascular or orthopedic surgeries. Summary: Promoting regional anesthesia/analgesia in ICU surgical/trauma patients could undoubtedly limit the risk of complications, ICU/hospital stay, and improve patient's outcome. The use of regional anesthesia permits a high doses opioid use limitation which is mandatory and should be considered as feasible and well tolerated in ICU.